(untitled) (Global Journal of Science Frontier Research, 2015)
The scarcity of natural populations of Anibarosaeodora in Brazil is well known and it has been attributed to the over-exploitation for extraction of its trunk wood essential oil for perfumery industry. The leaves of cultivated trees of this species could be a new source for future sustainable exploitation for the same purpose. Leaf oils from 35 trees of A. rosaeodora ("paurosa") obtained by hydrodistillation were analyzed by gas chromatography/mass spectrometry. High variation in yields (1.15% to 4.21%) and in linalool content (38.48% to 71.05%) were observed. Additionally, leaf oils of A. parviflora ("macacaporanga"), commonly confused as A. rosaeodorawere analized. Linalool was the major compound in A. parviflora essential oils, but in considerable smaller amount (21.30% and 12.64%) when compared to A. rosaeodora. Anibaparviflora oils were different from those of A. rosaeodora, showing a high amount of βphellandrene (21.06% and 23.60%), and lacking the presence of α-, β-and γ-eudesmol, and 7epi-α-and 10-epi-γ-eudesmol.